MAKNA DENOTATIF DAN KONOTATIF DALAM BAHASA WOTU (Denotative and Connotative Meaning in Wotu Language) - Adri Adri (Balai Bahasa Sulawesi Selatan, 2020)
The Wotu language is a local language that is almost extinct due to the speaker’s number is relatively small; thus, it needs to be preserved by doing documentation. Documentation, in this case, is conducting through research. The research documentation results can be used as teaching materials for teaching the Wotu language in school. It is one of the efforts to preserve the Wotu language. This study examines the denotative and connotative meanings of the Wotu language. The semantics of the Wotu language has not been investigating yet; thus, it is necessary to research this aspect. The study employed a descriptive qualitative method with data sources were gaining from primary and secondary data. Preliminary data obtained directly from native speakers, while secondary data obtained from writings or literary work that used the Wotu language. The techniques used were giving some questions and face to face techniques. The results showed that denotative and connotative meanings were found in some cases in the Wotu language. It only had connotative meanings and did not have denotative meanings. The connotative meanings in the Wotu language also varied, both with negative, neutral, and positive connotations. However, based on the data found, the negative connotations were more founding than other connotations.AbstrakBahasa Wotu adalah salah satu bahasa daerah yang jumlah penuturnya tergolong sedikit sehingga perlu dilestarikan dengan pendokumentasian. Pendokumentasian dalam hal ini melalui penelitian. Hasil dokumentasi penelitian bahasa Wotu dapat dijadikan bahan ajar untuk pengajaran bahasa Wotu di sekolah. Hal ini sebagai salah satu upaya pelestarian bahasa Wotu. Semantik bahasa Wotu belum tersentuh sehingga perlu dilakukan penelitian tentang hal ini. Penelitian ini mengkaji makna denotatif dan makna konotatif. Tujuan penelitian untuk mendeskripsikan makna denotatif dan makna konotatif. Teknik yang digunakan adalah teknik pancing dan teknik cakap semuka. Sumber data dari data primer dan data sekunder. Data primer langsung diperoleh dari penutur asli dan data sekunder dari tulisan atau karya sastra yang berbahasa Wotu. Hasil penelitian menunjukkan bahwa makna denotatif dan konotatif dalam bahasa Wotu ditemukan beberapa contoh yang hanya memiliki makna konotatif dan tidak memiliki makna denotatif. Makna konotatif yang ada dalam bahasa Wotu pun bervariasi, baik yang berkonotasi negatif, netral, maupun positif. Akan tetapi, berdasarkan data yang ditemukan, konotasi negatif lebih banyak dibanding konotasi-konotasi yang lainnya.